Monetizing Environmental Impacts of Nuclear Power: Cost-Benefit Analysis Using Social Cost of Carbon - Sung-Tae Lee; Sun-Moon Jung (SAGE Open, 2024)
This paper conducts a comprehensive cost-benefit analysis of nuclear energy’s contribution to climate change mitigation, with a focus on its potential to reduce the social cost of carbon (SCC). For 31 countries, we employ a four-step methodology to estimate SCC, comparing it against the lifetime costs associated with nuclear power generation. The Upstate New York case study in 2019 reveals that its three nuclear power plants could save approximately $675 million of the social cost of carbon (SCC) annually. Our SCC analyses suggest that the currently operating nuclear power plants worldwide can save the SCC, corresponding to 2.6% of the United States’ annual GDP. According to our cost-benefit analysis, among several countries that operate nuclear reactors, the US and China exhibit high environmental benefits from nuclear power, whereas other countries earn net environmental losses from it. Our study’s robust data analysis methods ensure the reliability and validity of our conclusions, enhancing the relevance of our findings for informing policy decisions. Despite variations in net benefits influenced by societal SCCs and levelized costs of energy (LCOE), nuclear energy emerges as a crucial component in transitioning to a zero-carbon grid. Our study advocates for the use of SCC analysis to incentivize the adoption of low-carbon energy sources.